THE CORRELATION STUDY OF PREGNANT WOMEN'S MALNUTRITION WITH ABORTUS INCIDENCE IN THE TAMBAKBOYO HEALTH CENTER AREA, TAMBAKBOYO SUB-DISTRICT, TUBAN DISTRICT - Nafies, Dian; Lilia Faridatul Fauziah; Purnama Sari, Dwi Kurnia (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Malnutrition was a medical condition caused by unbalanced nutritional intake in the form of macronutrients and micronutrients. Malnutrition was at risk for abortion. The high number of malnutrition accompanied by abortion, so this study aims to determine whether there is a correlation study of malnutrition in pregnant women with the incidence of abortion at the Tambakboyo Health Center, Tambakboyo District, Tuban Regency. The research design was correlational analytic with the population of all pregnant women who were examined (216) by collecting data through medical records. The sampling technique is simple random sampling (140). The independent variable is malnutrition of pregnant women, the dependent variable is the incidence of abortion. Analysis with contingency coefficient test with️ = 0.05. The results were obtained from data on 140 pregnant women, for malnutrition who experienced abortions based on BMI almost half (46%), based on Chronic energy deficiency almost half (29%) and based on anemia almost half (30%). From the data analysis, the results were obtained in the form of abnormal BMI sig 0.000, in the form of chronic energy deficiency sig 0.004, in the form of anemia sig 0.000. Because sig < 0.05, Hi is accepted, which means that there is a significant relationship between malnutrition in pregnant women and the incidence of abortion in the form of BMI, CED and anemia. The conclusion of this study is that there is a correlation between malnutrition in pregnant women and the incidence of abortion in the Tambakboyo Community Health Center, Tambakboyo District, Tuban Regency. Thus, it is hoped that health workers will provide IEC on balanced nutrition to prospective mothers before preparing for pregnancy, both through formal and informal channels.